Analisis Simulasi Hubungan Suhu Sintering Dengan Nilai Kekerasan Dan Kekuatan Patah Keramik Alumina - Marnanda Seragih; Sahara Lubis; Juliandi Siregar (Universitas Labuhanbatu, 2020)
This research uses variable sintering temperature of 1300 0C, 1400 0C, 1500 0C and 1600 0C mixed with mullite additives 0%, 10%, 15%, 20% and 25%. As parameters of the study are the vickers hardness and bending strength. In this study a computational simulation has been designed with the Matlab program to analyze the relationship between the Vickers Hardness and bending strength to the sintering temperature of alumina ceramics (Al2O3) with variations in the addition of mullite additives.The best result of the hardness value which is close to the literature value is the 25 % mullite additive composition at a sintering temperature of 1600 0C which is 475 kgf / mm2. The best results of fracture strength values close to the literature value is the composition of the mullite additive 20% at a sintering temperature of 1600 0C which is 45,800 lbf / in2. From the results of simulation analysis for hardness and strength of the fractures can be obtained a constant change due to the constant increase in sintering temperature.Keywords: Matlab, Vickers Hardness and Bending Strength, Alumina Ceramics, Mullit.